Increasing the midsole bending stiffness of shoes alters gastrocnemius medialis muscle function during running - Sasa Cigoja (Nature Portfolio, 2021)
Abstract In recent years, increasing the midsole bending stiffness (MBS) of running shoes by embedding carbon fibre plates in the midsole resulted in many world records set during long-distance running competitions. Although several theories were introduced to unravel the mechanisms behind these performance benefits, no definitive explanation was provided so far. This study aimed to investigate how the function of the gastrocnemius medialis (GM) muscle and Achilles tendon is altered when running in shoes with increased MBS. Here, we provide the first direct evidence that the amount and velocity of GM muscle fascicle shortening is reduced when running with increased MBS. Compared to control, running in the stiffest condition at 90% of speed at lactate threshold resulted in less muscle fascicle shortening (p = 0.006, d = 0.87), slower average shortening velocity (p = 0.002, d = 0.93) and greater estimated Achilles tendon energy return (p ≤ 0.001, d = 0.96), without a significant change in GM fascicle work (p = 0.335, d = 0.40) or GM energy cost (p = 0.569, d = 0.30). The findings of this study suggest that running in stiff shoes allows the ankle plantarflexor muscle–tendon unit to continue to operate on a more favourable position of the muscle’s force–length–velocity relationship by lowering muscle shortening velocity and increasing tendon energy return.